Effect of Product Quality and Service Quality Against Consumer Satisfaction Case Study On UKM Wawarungan Ijot, Cimahi City - Nurhaidah Sari, Ega; Dirgantara Asikin, Doni (International Journal of Management Science and Information Technology, 2023)
This research was conducted on consumers of UKM Wawarungan Ijot, Cimahi City. The purpose of this research is to find out how much influence the influence of Product Quality and Service Quality has on Customer Satisfaction either partially or simultaneously. The research method that will be used in this research is descriptive and associative method. In this study, the unit of analysis is the individual, namely the consumer of MSMES Wawarungan Ijot Cimahi. The sample in this study were 114 respondents. The sampling technique is random sampling. The research method uses multiple linear regression. The results of the study show that there is a simultaneous positive effect on product quality and service quality on MSME consumer satisfaction in Wawarungan Ijot Cimahi. The implications of the Wawarungan Ijot Cimahi MSME research can make various improvements to product resilience, new innovations, consistency in service.